Local Hybrid Newspapers Typology: Three Cases From Radar Media Group Members In Indonesia - Budi NUGRAHA; Udi RUSADI; Jamalullail JAMALULLAIL (International Journal of Environmental, Sustainability, and Social Science, 2022)
The survival of print media in the internet and social media era is increasingly threatened, especially with the increase in paper prices and the shift of advertisers to online media. One common strategy that print newspapers adopt is to establish an online version of the print newspaper and, accordingly, become a hybrid newspaper. This paper explores how three hybrid local newspapers in Indonesia reacted to the challenges of digitalization in three different market structures: monopolistic, duopoly, and oligopoly. We see this as a form of media behavior in dealing with market structures formulated in the structure-conduct-performance (SCP) paradigm. The analysis attempts to find a typology of local hybrid newspapers based on the three interrelated components of SCP. The data of this study were obtained from interviews with top management of the three newspapers, accompanied by primary and secondary literature studies. The study found different practices of the three newspapers responding to their respective markets in terms of organizational structure, content, and support channels, online and offline. It allows us to formulate three types of mixed media: social hybrid media, business hybrid media, and Omni hybrid media. Strategy carried out by the business hybrid media allows gain profits and improve employee welfare